2014
DOI: 10.1007/s10549-014-2980-0
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA mutation evaluation in a prospective triple-negative breast cancer registry: implications for hereditary breast and/or ovarian cancer syndrome testing

Abstract: NCCN guidelines recommend genetic testing for all triple-negative breast cancer (TNBC) patients aged ≤60 years. However, due to the lack of prospective information in unselected patients, these guidelines are not uniformly adopted by clinicians and insurance carriers. The aim of this study was to determine the prevalence of BRCA mutations and evaluate the utility of NCCN guidelines in unselected TNBC population. Stage I–IV TNBC patients were enrolled on a prospective registry at academic and community practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 30 publications
8
111
2
2
Order By: Relevance
“…This is a much higher percentage than the 10-20% seen in other studies of patients with TNBC unselected for family history. 7,8,15 Considering the results from both our diagnostic and research cohorts, we wondered whether the high prevalence of mutation c.4183C4T in the Zillertal and LIV region is associated with an increased incidence of cancer. Detailed regional data from the Tyrolean Cancer Registry confirmed an increased risk for breast and ovarian cancer especially in the region of Zillertal with SIRs of 1.23 for breast cancer below the age of 50 and 2.13 years for ovarian cancer below the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…This is a much higher percentage than the 10-20% seen in other studies of patients with TNBC unselected for family history. 7,8,15 Considering the results from both our diagnostic and research cohorts, we wondered whether the high prevalence of mutation c.4183C4T in the Zillertal and LIV region is associated with an increased incidence of cancer. Detailed regional data from the Tyrolean Cancer Registry confirmed an increased risk for breast and ovarian cancer especially in the region of Zillertal with SIRs of 1.23 for breast cancer below the age of 50 and 2.13 years for ovarian cancer below the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the prevalence of BRCA mutations in unselected tnbc patients [18][19][20][21] , and their authors have suggested that tnbc patients should be considered for BRCA1 and BRCA2 genetic testing based on the evidence of high BRCA mutation prevalence in unselected tnbc patients. Muendlein et al 18 assessed the prevalence of BRCA mutation in 100 unselected tnbc patients.…”
Section: Discussionmentioning
confidence: 99%
“…Los cánceres de mama asociados a la mutación del gen BRCA1 son con frecuencia negativos para la presencia de receptores de estrógeno, progesterona, y la sobreexpresión de HER-2/Neu (triple negativo) (30)(31)(32)(33). El 90 % de los tumores debidos a mutaciones en BRCA1 son triple negativos por inmunohistoquímica (19); además, en pacientes con tumores TN, la probabilidad de estar ligados a mutaciones BRCA1 es mayor que en las clasificadas como NO triple negativo, con un RR = 5,65 (IC 95 %: 4,15-7,69) (34); sin embargo, se desconoce la proporción exacta de tumores triple negativos que poseen mutaciones en BRCA1 (20).…”
Section: ¿Varía El Tipo De Cáncer De Seno Según La Mutación?unclassified